2011
DOI: 10.1051/0004-6361/201117099
|View full text |Cite
|
Sign up to set email alerts
|

Flux emergence within mature solar active regions

Abstract: Aims. Recent insterest in flux emergence within mature active regions has led to several observational studies. Our aim is to model such a scenario and investigate the evolution of the system. Methods. We solve the 3D MHD equations numerically with a Lagrangian-remap scheme. The mature active region is modelled, in the initial condition, with a potential field. The smaller emerging region is a twisted flux tube and is placed between the two polarities of the mature region. The polarities of the new flux are al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 15 publications
1
10
0
Order By: Relevance
“…They were originally reported by López Fuentes et al (2000) and observed later in other works (see, e.g., Li et al, 2007;Chandra et al, 2009;Luoni et al, 2011). Their presence in emerging flux-ropes has been found by numerical simulations (Archontis and Hood, 2010;MacTaggart, 2011;Jouve, Brun, and Aulanier, 2013). Luoni et al (2011) compared the helicity-sign inferred from the orientation of magnetic tongues, observed in line-of-sight magnetograms, with other known helicity sign proxies for a sample of 40 ARs.…”
Section: Introductionmentioning
confidence: 66%
“…They were originally reported by López Fuentes et al (2000) and observed later in other works (see, e.g., Li et al, 2007;Chandra et al, 2009;Luoni et al, 2011). Their presence in emerging flux-ropes has been found by numerical simulations (Archontis and Hood, 2010;MacTaggart, 2011;Jouve, Brun, and Aulanier, 2013). Luoni et al (2011) compared the helicity-sign inferred from the orientation of magnetic tongues, observed in line-of-sight magnetograms, with other known helicity sign proxies for a sample of 40 ARs.…”
Section: Introductionmentioning
confidence: 66%
“…One area of significant interest is the emergence of both twisted and untwisted flux ropes through the photosphere into the lower corona, and how they affect the existing field in this region (MacTaggart & Hood 2009a,b;Fang et al 2010;Moreno-Insertis & Galsgaard 2013;MacTaggart 2011). One might ask whether a braided/tangled flux tube would be able to emerge from the convection zone?…”
Section: Discussionmentioning
confidence: 99%
“…This is based on the numerical experiments of Wilmot-Smith et al (2009, 2011, where a family of braided magnetic fields were created using series of n opposing pairs of rotations through an angle π rad at staggered distances along the tube's length. In this case we use 4 pairs of opposing twist so this would be a B4 field (in the notation of Wilmot-Smith et al (2009) this would be an E4 field, but we prefer "B" to indicate "braided").…”
Section: B4 Braidmentioning
confidence: 99%
“…Many of them use boundary conditions to insert the emerging flux in the domain (Chen and Shibata, 2000;Dubey et al, 2006;Zuccarello et al, 2008Zuccarello et al, , 2009Kusano et al, 2012), whereas others solve the buoyant rise of the emerging flux from below the photosphere self-consistently (MacTaggart and Hood, 2009a;MacTaggart, 2011;Leake et al, 2010). …”
Section: Emerging Flux As a Trigger For Eruptionsmentioning
confidence: 99%